2017
DOI: 10.1093/mnras/stx298
|View full text |Cite
|
Sign up to set email alerts
|

Temporal resolution of a pre-maximum halt in a classical nova: V5589 Sgr observed with STEREO HI-1B

Abstract: Classical novae show a rapid rise in optical brightness over a few hours. Until recently the rise phase, particularly the phenomenon of a pre-maximum halt, was observed sporadically. Solar observation satellites observing Coronal Mass Ejections enable us to observe the pre-maximum phase in unprecedented temporal resolution. We present observations of V5589 Sgr with STEREO HI-1B at a cadence of 40 min, the highest to date. We temporally resolve a pre-maximum halt for the first time, with two examples each risin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Those features together with the presence of a multi- color pre-maximum halt and the smooth post-maximum evolution suggest that KSP-OT-201509a is a rapidly evolving classical nova. Indeed, the lightcurve shown in Figure 2 shows similarities with other well-sampled fast galactic novae such as V5589 Sgr (Eyres et al 2017, see §5 for a more detailed discussion). Finally, the observed peak luminosity/decline rate ratio is in good agreement with established empirical relations.…”
Section: The Nature Of Ksp-ot-201509asupporting
confidence: 53%
“…Those features together with the presence of a multi- color pre-maximum halt and the smooth post-maximum evolution suggest that KSP-OT-201509a is a rapidly evolving classical nova. Indeed, the lightcurve shown in Figure 2 shows similarities with other well-sampled fast galactic novae such as V5589 Sgr (Eyres et al 2017, see §5 for a more detailed discussion). Finally, the observed peak luminosity/decline rate ratio is in good agreement with established empirical relations.…”
Section: The Nature Of Ksp-ot-201509asupporting
confidence: 53%
“…The authors reported evidence of pre-maximum halts, detecting two short duration dips during the rise to maximum, as predicted by [10]. The halts are precursors of the onset of mass loss [6]. The data of V5589 Sgr have been re-analyzed by [38], who performed a different background subtraction.…”
Section: Novae: the Pre-maximum And Maximum Stagesmentioning
confidence: 89%
“…The energy flux drops when convection in the expanding envelope becomes inefficient near the envelope surface and opacity decreases. Dips have been observed in RS Oph and KT Eri [11] and in V5589 Sgr (see below) [6].…”
Section: Novae: the Pre-maximum And Maximum Stagesmentioning
confidence: 94%
See 1 more Smart Citation
“…This means that the time between eruptions, although substantially different for some of the models, cannot be used alone as an observational tool to determine the composition of the donor envelope. Another example may be the estimated modeled accretion rate for the classical nova V5589 Sgr in Eyres et al (2017), which is based on solar composition accreted material. They state that since the donor in the system is a sub-giant, the accreted material may be somewhat enriched, and thus the estimated accretion rate may be somewhat different.…”
Section: Discussionmentioning
confidence: 99%